Human Trafficking in Southeast Asia: Results from a Pilot Project in Vietnam - Ngan Dinh; Conor Hughes; James W. Hughes; Margaret Maurer-Fazio (Institute for the Study of Labor (IZA), 2014)
Human trafficking is one of the most widely spread and fastest growing crimes in the world. However, despite the scope of the problem, the important human rights issues at stake and the professed intent of governments around the world to put an end to "modern day slavery", there is very little that is actually known about the nature of human trafficking and those most at risk as potential victims. This is due in large part to the difficulty in collecting reliable and statistically useful data. In this paper we present the results of a pilot study run in rural Vietnam with the aim of overcoming these data issues. Rather than attempt to identify victims themselves, we rely on the form rural migration often takes in urbanizing developing countries to instead identify households that were sources of trafficking victims. This allows us to construct a viable sampling frame, on which we conduct a survey using novel techniques such as anchoring vignettes, indirect sampling, list randomization and social network analysis to construct a series of empirically valid estimates that can begin to shed light on the problem of human trafficking.
Keywords: J47; J61; J82; K37; K42; O15; 330; human trafficking; labor migration; Vietnam; household survey; indirect sampling; social network analysis; pilot study; public policy